2021
DOI: 10.1161/strokeaha.120.033775
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Field Assessment Stroke Triage for Emergency Destination Scale Use by Paramedics: Mobile Stroke Unit First-Year Experience

Abstract: Background and Purpose: Field Assessment Stroke Triage for Emergency Destination (FAST-ED) scale is a helpful tool to triage patients with stroke in the field. However, data on its reliability in the prehospital setting are lacking. We aim to test the reliability of FAST-ED scale when used by paramedics in a mobile stroke unit covering a metropolitan area. Methods: As part of standard operating mobile stroke unit procedures, paramedics initially evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
(48 reference statements)
0
10
0
1
Order By: Relevance
“…Such a gap may contribute to a poorer performance of the scales in the pre-hospital phase compared with their performance during an in-hospital evaluation due to difficulties in identifying subtle neurological impairment. However, a recent study showed an excellent reliability in the FAST-ED score obtained by paramedics compared with the score obtained by vascular neurologists [39], thus suggesting that differences in modalities of clinical evaluation may have only a minor impact on our findings. Finally, our study was based on a limited number of patients with LVO, thus limiting its power.…”
Section: Discussionmentioning
confidence: 59%
“…Such a gap may contribute to a poorer performance of the scales in the pre-hospital phase compared with their performance during an in-hospital evaluation due to difficulties in identifying subtle neurological impairment. However, a recent study showed an excellent reliability in the FAST-ED score obtained by paramedics compared with the score obtained by vascular neurologists [39], thus suggesting that differences in modalities of clinical evaluation may have only a minor impact on our findings. Finally, our study was based on a limited number of patients with LVO, thus limiting its power.…”
Section: Discussionmentioning
confidence: 59%
“…LVO patients in the intervention group ( n = 240) had better management metrics and better outcomes than did LVO patients in the pre-intervention group (34.6 vs. 23.7%; P = 0.014) [21]. Similarly, use of an LVO scale has been studied in a telemedicine-equipped MSU, with positive effects [22].…”
Section: Referral Models For Acute Stroke Drip and Ship Vs Mothershipmentioning
confidence: 99%
“…While they can be administered swiftly and reliably in the prehospital setting, the sensitivity and specificity of these scales are variable and have achieved only moderate success in discriminating stroke mimics from strokes. 27–29 Furthermore, no clinical scale can meaningfully differentiate hemorrhagic from ischemic stroke (particularly LVO stroke) and so neuroimaging remains paramount in diagnosis. Identifying the type and etiology of stroke can be a diagnostic challenge for the DTA approach.…”
Section: What Is the Role Of The Ed?mentioning
confidence: 99%